Water Memory and Homeopathy Result from Trimmed Chains of Water-Crystallites - Auguste Meessen (New Insights into Physical Science Vol. 13, 2021)
Biologically active molecules create substitutes in liquid water by means of a remarkable physical process. These molecules have indeed a charged part that can oscillate at a characteristic low frequency f. Its electric field aligns the dipoles of close water molecules and forms small polarized “water pearls” of identical size. They constitute chains, where they are set in oscillatory rotation at the frequency f, as soon as their length allows for standing waves. These chains are thus trimmed and become information carriers. They produce themselves an electric field, oscillating at the frequency f. It causes multiplication of identical chains, which can also excite the specific receptors of the chosen active molecules by resonance. This process is theoretically proven and confirmed by measurements.